Vision Influence on Whole-Body Human Vibration Comfort Levels - Maria Lúcia Machado Duarte; Matheus de Brito Pereira (Shock and Vibration)
The well being of people needs to be a priority in the modern world. In that respect, vibration cannot be one more cause of stress. Besides that, vibration comfort is very important, since high levels may cause health or even tasks' accomplishment problems. Several parameters may influence the levels of vibration a human being supports. Among them, one can mention the influence of gender, age, corporeal mass index (CMI), temperature, humor, anxiety, hearing, posture, vision, etc. The first three parameters mentioned were already investigated in previous studies undertaken by GRAVI (Group of Acoustics and Vibration) researchers. In this paper, the influence of vision is evaluated. The main objective with this series of tests performed is to try to quantify in a future the influence of each parameter in a global vibration comfort level. Conclusions are presented for the parameter investigated.